Risk assessment of polluted glass insulator using leakage current index under different operating conditions - Salem, Ali Ahmed; Abd-Rahman, Samir Ahmed; Al-Gailani, Samir Ahmed; Salam, Zainal; Kamarudin, Muhammad Saufi; Zainuddin, Hidayat; Mohd Yousof, Mohd Fairouz (IEEE, 2020)
In this article, an innovative approach to assess the risk of uniform/non-uniform pollution and wet high voltage glass insulator is proposed. The assessment is based on a new index, named as Rhi, which is derived from the 3rd, 5th and 7th harmonics of the leakage current. Two 33 kV strings of cap and pin glass insulators having three units with different profiles are employed to evaluate the risk level, based on measured critical voltage gradient (Ec). Critical voltage stress tests are executed on the contaminated insulators under different ratios of lower to upper surface (J) and wetting rates. Furthermore, the effects of ratio of soluble deposit density (ESDD) to non-soluble deposit density (NSDD) on the flashover occurrence are analyzed. It was found that the insulator profile has significant influences on the likelihood of flashover which is estimated as 38% and 24% for type A and B insulators, respectively. From the results, it can be concluded that the proposed Rhi index is able to predict the risk level of the insulator and the probability of flashover occurrence more accurately than the 5th/3rd index, which is widely published in literature.